IDENTIFIKASI KETERAMPILAN GEOMETRI SISWA LAKI-LAKI DAN PEREMPUAN SMP BERDASARKAN TINGKATAN VAN HIELE DALAM MENYELESAIKAN SOAL BANGUN DATAR - Yunianta, Tri Nova Hasti; Lusiyati, Lusiyati (Satya Widya, 2020)
This qualitative descriptive study aims to identify the geometry skills of both male and female secondary school (SMP) students based on Van Hiele level in solving a flat wake up problem. The selection of the subject using purposive sampling technique consisting of 2 students (1 male and 1 female) of 35 students in class VIII A SMP Negeri 2 Sumowono who have been working on a test adapted from the project CDASSG Usiskin ie VHGT test and the result has a level of geometry thinking van Hiele. This study will identify differences in geometry skills that exist in female and male students who have geometric thought levels of van Hiele. Data collection techniques using test methods, interviews and documentation. The results showed that both subjects had a level of geometric thinking van Hiele and both had visual, verbal, drawing, logic and applied skills differentiating in solving the problem.